(untitled) (Journal of the Bangladesh Agricultural University, 2017)
The study aims to examine the profitability and forward linkage analysis of poultry feed covering Dhaka, Gazipur, Narsingdi, Kishoreganj and Mymensingh districts. In total 30 feed mills which categorized such as high, medium and low quality on the basis of feed conversion ratio along with 45 dealers; 15 sub-dealers and 120 farmers purposively. The primary data were collected during March 2013 to March 2014 by using survey schedule, KII and FGD. In addition, the secondary data were collected from different government documents. It is evident that the cost of feed was found Tk. 39295, Tk. 38643 and Tk. 37218 per MT (metric ton) respectively for high, medium and low quality feed mills. The gross returns were found Tk. 43160, Tk. 42330 and Tk. 40500 per MT and gross margin was Tk. 6486, Tk. 5957 and Tk. 5285 per MT respectively. The net returns were found Tk. 3865, Tk. 3687and Tk. 3279.2 per MT respectively. It indicates that total gross return, gross margin and net return of high quality feed mill is higher than medium and low quality feed mill. It is also evident that about 60% of raw materials were purchased from Dinajpur, Rangpur, Rajshahi, Jamalpur and coastal areas namely Bagergerhat, Chittagong and Khulna where as 100 percent of feed additives were imported. The unavailability of raw materials was the major problems for feed mills operation which influenced feed price and quality. If these problems could be solved within a reasonable time, stakeholders would be able to get more benefits and run business smoothly. J. Bangladesh Agril. Univ. 14(2): 201-208, December 2016